Khitan pada Wanita dalam Tinjauan Hadis dan Medis - Gusnanda, Gusnanda; Wijaya, Roma (UIN Sultan Syarif Kasim Riau, 2023)
This article purpose to resolve the controversy about female circumcision from the perspektive of hadith and health science. The problem is religius order about circumcision for women is clearly contained in the hadith of the Prophet SAW. This hadith is believed have a goodness for women. But this religious argument contradicts the world view of health. Circumcision is actually considered a practice detrimental to women's groups. Reinforcer the perspektive The Indonesian Ministry of Health issued a circular letter concerning the Prohibition of Medicalization of Female Circumcision with number: HK.00.07.1.3.1047a. on April 20, 2006. This study is literature research. To analyse the issue, this study uses the paradigm of fiqh al-hadis and modern health theory regarding female circumcision. The conclusion in this research is the Islamic recommendation regarding female circumcision and the disclaimer of the Indonesian Ministry of Health are not fundamentally contradictory. The hadiths advocating circumcision are not absolute. In Islamic fiqh, it is also regulated how the procedure for female circumcision. For example, the right time to do circumcision and the application process so that. This provision was formulated with the aim of safeguarding women's rights in accordance with religious goals. Although this provision actually still originates from the product of patriarchal fiqh and cannot be separated from the developing cultural construction. However, this provision is well established and must be universally understood. Meanwhile, the circular letter from the Ministry of Health is not absolute. This policy must be understood in a certain context because it departs from cases that occurred in the field. The important point is that circumcision for women must be carried out in accordance with the correct methods and procedures, by not spending the entire labium minora on the female genitalia. Abstrak: Tulisan ini bertujuan untuk menyelesaikan kontroversi masalah khitan bagi perempuan dalam perspektif hadis dan medis. Letak persoalannya yakni: perintah khitan bagi perempuan termuat jelas dalam hadis Rasul SAW. Anjuran hadis tersebut diyakini mengandung sejumlah kebaikan bagi perempuan. Tetapi dalil agama ini bertolak belakang dengan pandangan dunia kesehatan modern. Khitan justru dianggap sebagai praktik merugikan kelompok perempuan. Mempertegas masalah itu Kementerian Kesehatan RI mengeluarkan surat edaran tentang Larangan Medikalisasi Sunat Perempuan dengan nomor: HK.00.07.1.3.1047a. pada 20 April 2006. Studi ini merupakan library research (kajian kepustakaan). Dalam menganalisis persoalan, studi ini menggunakan paradigma fiqh al-hadis dan teori kesehatan modern menyangkut sunat bagi perempuan. Kajian dalam tulisan ini menyimpulkan bahwa anjuran Islam tentang khitan bagi perempuan dan sikap Kementerian Kesehatan RI tidaklah bertentangan secara hakiki. Hadis-hadis yang menganjurkan perempuan berkhitan tidaklah bersifat mutlak. Dalam fiqih Islam juga diatur bagaimana tata cara khitan bagi perempuan. Misalnya, waktu yang tepat melakukan khitan dan proses aplikasinya. Ketentuan ini dirumuskan bertujuan untuk menjaga hak-hak perempuan sesuai dengan tujuan agama. Meskipun ketentuan ini sesungguhnya masih berasal dari produk fiqih patriarki dan tidak bisa dilepaskan dari kunstruksi budaya yang berkembang. Akan tetapi, ketentuan ini sudah mapan dan harus dipahami secara universal. Sedangkan surat edaran Kementerian Kesehatan juga bersifat tidak mutlak. Kebijakan ini mesti dipahami dengan konteks tertentu karena beranjak dari kasus-kasus yang terjadi di lapangan. Poin pentingnya bahwa pelaksanaan khitan bagi perempuan harus dilakukan sesuai dengan metode dan prosedur yang benar, dengan tidak menghabiskan seluruh labium minora pada alat kelamin wanita.